Russian Energy Politics: Energy Policy Implications for National and Global Stability 2024-2025 - Amirunnaufal, Mohamad; Aurora, Allynka First (Journal of Social Dynamics and Governance, 2025)
Economic development and political stability in Russia, as well as its opportunities to influence international politics, strongly depend on the ambitious energy policy of the state. Russia's energy policy is realized in the complex international framework because Russia is a member of the World Trade Organization and a key participant in energy integration processes. In 2015, it was ranked second in the Global Energy Architecture Performance Index Report published by the World Economic Forum. It renewed its position in the Global Energy Index Report 2017 as the second-best energy market in the world. It also ranked as the country with the highest score in the global ranking of optimal conditions for investment in distributed mustache. Additionally, it has the most favorable investment criteria in the BRICS group. The World Bank published the ranking of "the countries-leaders in the matters of obtaining the new renewable energy," and Russia is leading in this ranking. Energy is vital for the functioning of modern societies and economies, ensuring energy security, climate stabilization, and industrial development, and facilitating the growth of new sectors. The role of energy in the global environment has become increasingly complicated since decision-makers have to concurrently address a growing range of energy-related social, economic, and security concerns. As a rising power, Russia faces some key challenges regarding its energy policies of regulating the energy market and modernizing the energy infrastructure. This research aims to analyze Russia's energy politics in the context of national and global stability in 2024-2025.